Improved high-resolution characterization of hydraulic conductivity through inverse modeling of HPT profiles and steady-state hydraulic tomography: Field and synthetic studies - Zhao, Zhanfeng; Illman, Walter A. (Journal of hydrology (Amsterdam), 2022)
•Inverse modeling approach proposed to invert cm-scale K from HPT surveys.•Based on inverted K, a new power-law model was developed for HPT surveys at NCRS.•The site-specific model predicted K values that correspond well with permeameter K.•Integrating HPT-inverted K into SSHT better defined sharp boundaries of a K field. Direct-push based hydraulic profiling tool (HPT) and geostatistically-based hydraulic tomography (HT) are two promising techniques for the high-resolution estimation of hydraulic conductivity (K) for unconsolidated sediments. Although HPT surveys could be conducted rapidly, relating the 1.5-cm resolution injection logging profiles to K always involve the upscaling of centimeter-scale measurements to coarser intervals for the development of site-specific formulae. On the other hand, K fields reconstructed by HT could be smooth when pumping test data are sparse. In this study, an inverse modeling approach was firstly utilized to estimate K values directly from HPT survey data for the glaciofluvial deposits at the North Campus Research Site (NCRS) in Waterloo, Ontario, Canada. A site-specific power-law relationship was generated for the NCRS to relate HPT profiles to the vertical distributions of K. Then, the proposed inverse modeling approach was evaluated with a two-dimensional synthetic aquifer under controlled conditions, and the estimated K profiles from inverse analysis of synthetic HPT surveys were incorporated into the steady-state HT. Results of the field study showed that K estimates from the developed formula corresponded better with K values from permeameter tests, than those estimated from the empirical model of McCall and Christy (2010) for HPT surveys. Moreover, through synthetic experiments, we demonstrated that integration of K values inverted from HPT into steady-state HT analyses yielded K tomograms that were significantly better than the geostatistical inversion results relying on pumping test data alone. Overall, this study highlights the need in developing site-specific formulae for the HPT and the joint implementation of HPT and HT techniques for the more cost-effective high-resolution characterization of subsurface heterogeneity.